2002
DOI: 10.1002/ijc.10600
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene, NMES1, downregulated in human esophageal squamous cell carcinoma

Abstract: To isolate genes with different expression levels in human esophageal SCC, SSH and reverse Northern were performed between cancer tissue and its normal counterpart. Among the differentially expressed genes identified, we report here cDNA corresponding to a 0.88 kb mRNA (NMES1), whose expression was observed in all 36 adjacent normal esophageal mucosae, while 31 (86%) matched cancer tissues showed a marked reduction or complete lack of its expression. Sequence analysis of its full-length cDNA revealed a gene en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 11 publications
5
30
0
Order By: Relevance
“…RRAD, encoding a protein belonging to a subfamily of Ras-related GTPbinding proteins (32), has been recently found aberrantly methylated in mesotheliomas in relationship with SV40 infection (33). Hypermethylation of NMES1 has not been previously noted in any tissue, although this gene has been reported to be expressed in normal but not in malignant esophageal tissues (34).…”
Section: Discussionsupporting
confidence: 46%
“…RRAD, encoding a protein belonging to a subfamily of Ras-related GTPbinding proteins (32), has been recently found aberrantly methylated in mesotheliomas in relationship with SV40 infection (33). Hypermethylation of NMES1 has not been previously noted in any tissue, although this gene has been reported to be expressed in normal but not in malignant esophageal tissues (34).…”
Section: Discussionsupporting
confidence: 46%
“…The functional consequences of NMES1 induction by TLR stimulation in macrophages are presently unknown. A previous study suggested that NMES1 may have a role as a tumor suppressor (22). Given that inflammation has been closely associated with carcinogenesis, elevation of NMES1 in inflammatory diseases may be a protective mechanism to prevent cellular transformation.…”
Section: Discussionsupporting
confidence: 43%
“…Jiang et al (11) has reported previously that amplification of the cyclin D1 gene is observed in about 25% of primary esophageal carcinomas from the People's Republic of China. In addition, altered gene expression of some growth-or differentiationrelated genes were found recently to be associated with ESCC (12)(13)(14). Therefore, abnormalities in oncogenes and tumor suppressor genes, as well as in cell cycle regulators may contribute to esophageal carcinogenesis and malignancy development.…”
Section: Introductionmentioning
confidence: 39%